The barrow culture of the Upper Dniester Basin in the 3 rd and 2 nd millennia BC: The Polish-Ukrainian research projects - Makarowicz, Przemysław; Romaniszyn, Jan; Rud, Vitalii (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
Since 2009, the international Upper Dniester Expedition has conducted field research (field-walking surveys, non-invasive and excavation) and analytical studies in the Eastern Transcarpathia. These investigations are part of a broader research programme – a study of ‘The Biocultural Borderland between the East and the West of Europe’. The projects concern a comprehensive reconnaissance of barrow cemeteries dated to the 3 rd and 2 nd millennia BC, located in the mixed forest-steppe and forest belt in the basin of the Upper Dniester River. For almost 1500 years, this type of funeral architecture shaped the ‘mortuary landscapes’ of the communities successively inhabiting that area. Hence, the barrow cemeteries are an important source for understanding the mechanisms and trajectories of cultural development in this part of Europe, and consequently the subject of intensive studies within several research projects. This article describes the aims and results of two already completed and one ongoing project in the Upper Dniester Basin. Thanks to the use of modern research methods, both in the field of archaeology and ‘archaeological sciences’, it has been possible to present a wide spectrum of regularities/principles concerning the ‘barrow landscapes’, the chronology of the creation of selected cemeteries, and the construction of regular, linear arrangements of barrows. Furthermore, the projects have and are providing large collections of archaeological (ceramic, lithic, metals, etc.), anthropological, archaeobotanical and archaeofaunal material for future analyses.
Keywords: Barrow cemeteries; Upper Dniester Basin; barrow landscapes; mortuary houses; Komarów culture